ANALISIS KESALAHAN BERBAHASA PADA ANAK USIA 2 TAHUN DITINJAU DARI TATARAN FONOLOGI - Fatimah, Siti (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2020)
Language is a communication tool used by speakers in everyday life. Language skills are needed for good interaction and the information exchange process. Therefore, language has been taught to children since birth and will develop according to their age and growth. Pshycologically, new children can say a word at the age of 2-3 years old. The tendency of language error that the children, who are 2-3 years old did, is an error in the field of phonology which is the children still difficult to pronounce one word perfectly. In addition, the children were often changed the phonemes of word, thus produce a different utterance from as well as it should have but still have the same meaning. The aim of study is to determine the level of children’s ability who are 2 years old in pronouncing a word perfectly. The research method used a descriptive qualitative method with the purpose is to describe with clearly and objectly the object of study. There are two children who became the object of this study, Arfa and Aimar, who are still two years old. The data collection was conduct by the researchers  as the main instrument that show the picture of animals to the children, then the children said it. The results of analysis shows that the much phonological error are the replacement an ellipsis/omission of phonemes. Therefore, there is a change in the sound of words that should be pronounced. Thus, in order to the acquistion of the children’s language more maximal, by training it in order to be better in spoken and a good guidance and stimulus by parent are needed.